2010
DOI: 10.1038/cdd.2010.109
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated waves of gene expression during neuronal differentiation of embryonic stem cells as basis for novel approaches to developmental neurotoxicity testing

Abstract: As neuronal differentiation of embryonic stem cells (ESCs) recapitulates embryonic neurogenesis, disturbances of this process may model developmental neurotoxicity (DNT). To identify the relevant steps of in vitro neurodevelopment, we implemented a differentiation protocol yielding neurons with desired electrophysiological properties. Results from focussed transcriptional profiling suggested that detection of non-cytotoxic developmental disturbances triggered by toxicants such as retinoic acid (RA) or cyclopam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
94
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 40 publications
4
94
0
Order By: Relevance
“…Indeed, cortical neurons derived from TAp73 −/− mice show a reduction in the levels of the neurotransmitters glutamate and GABA. Because neuronal differentiation is a complex biological process that is regulated by intrinsic pathways [46][47][48][49][50][51] and extrinsic signals, 52,53 it will be of interest to see whether these other metabolic effects of TAp73 also affect this biological process.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, cortical neurons derived from TAp73 −/− mice show a reduction in the levels of the neurotransmitters glutamate and GABA. Because neuronal differentiation is a complex biological process that is regulated by intrinsic pathways [46][47][48][49][50][51] and extrinsic signals, 52,53 it will be of interest to see whether these other metabolic effects of TAp73 also affect this biological process.…”
Section: Discussionmentioning
confidence: 99%
“…While there is no deus ex machina to solve all these challenges for the experimental toxicologist, the advent of pluripotent stem cells (PSCs) provides significant improvements (Baquié et al 2012;Leist et al 2008), enabling the impact of potentially toxic pesticides to be studied on virtually all types of cells without recourse to immortalized cell lines. Within the last 5 years, the European ESNATS consortium has been developing pluripotent stem cell-based toxicity tests, and first results demonstrate that such test systems may indeed become powerful tools (Krug et al 2013;Bolt 2013;Vojnits et al 2012;Kern et al 2013;Meganathan et al 2012;Kuegler et al 2010;Zimmer et al 2011a, b;Balmer et al 2012). The consortium has shown that complex functional endpoints can be transferred to in vitro test systems Kadereit et al 2012;Zimmer et al 2012).…”
mentioning
confidence: 99%
“…Nevertheless, an even deeper understanding of the established test systems is urgently needed. For example, neuronal differentiation in the ESNATS test systems is characterized by tightly coordinated waves of gene expression (Schulz et al 2009;Zimmer et al 2011;Gaspar et al 2012). This feature of the differentiating stem cells recapitulates expression waves of the developing central nervous systems in vivo.…”
Section: Future Directionsmentioning
confidence: 99%